2021
DOI: 10.1200/jco.2021.39.3_suppl.378
|View full text |Cite
|
Sign up to set email alerts
|

Overall survival from the phase 3 POLO trial: Maintenance olaparib for germline BRCA-mutated metastatic pancreatic cancer.

Abstract: 378 Background: POLO is the first phase 3 trial to evaluate maintenance therapy with the poly(ADP-ribose) polymerase inhibitor (PARPi) olaparib (O) in patients with metastatic pancreatic cancer (mPaC) and a germline BRCA mutation ( gBRCAm) whose disease had not progressed on first-line platinum-based chemotherapy (PBC). POLO demonstrated that patients had significantly longer progression-free survival (PFS; primary endpoint) with maintenance O than with placebo (P; hazard ratio [HR], 0.53; 95% confidence inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 0 publications
0
57
0
2
Order By: Relevance
“…15 However, there was no difference in overall survival, with median overall survival of 19.0 versus 19.2 months (HR, 0.83; 95% CI, 0.56-1.22), although there was a trend toward improved 36-month survival with olaparib (33.9% vs. 17.8%). 16 Olaparib maintenance therapy is now U.S. Food and Drug Administration approved and a standard-of-care option for patients with metastatic pancreatic adenocarcinoma with germline BRCA1/2 mutations after at least 16 weeks of first-line platinum-based chemotherapy.…”
Section: Brca1/2 Germline Mutationsmentioning
confidence: 99%
“…15 However, there was no difference in overall survival, with median overall survival of 19.0 versus 19.2 months (HR, 0.83; 95% CI, 0.56-1.22), although there was a trend toward improved 36-month survival with olaparib (33.9% vs. 17.8%). 16 Olaparib maintenance therapy is now U.S. Food and Drug Administration approved and a standard-of-care option for patients with metastatic pancreatic adenocarcinoma with germline BRCA1/2 mutations after at least 16 weeks of first-line platinum-based chemotherapy.…”
Section: Brca1/2 Germline Mutationsmentioning
confidence: 99%
“…The recently published POLO trial reported a significant prolongation of PFS with a PARPi maintenance treatment compared to a placebo [ 14 ]. Although showing a trend for prolonged overall survival (HR 0.83), the follow-up data of the trial could not demonstrate a significant survival benefit in the experimental arm [ 45 ]. This raises the question of whether prolonged PFS is a clinically meaningful endpoint.…”
Section: Resultsmentioning
confidence: 99%
“…PFS was chosen as the primary endpoint because patients with a g BRCA mutation who have received platinum chemotherapy have prolonged survival and receive multiple subsequent therapies, which could affect OS. The experts emphasised that some patients received PARPi subsequent to the trial [ 14 , 45 ]. The majority of experts (LOA = 90.1%) rated PFS as a clinically meaningful endpoint in patients with BRCA1/2 germline mutations and pancreatic cancer and therefore is a sufficient parameter for clinical use.…”
Section: Resultsmentioning
confidence: 99%
“…A recent phase III trial of olaparib (the POLO trial) displayed considerable improvement in PFS in germline BRCA-mutated metastatic PDAC patients who were sensitive to platinum agents in first-line therapy. 70 In addition, a recent study reported that ATM-mutant PDAC cells were responsive to the olaparib (PARPi) or the ATR inhibitor VE-822, and showed the that treatment with either of these inhibitors induced intense accumulation of DSBs and diminished tumor cell viability in vitro and in vivo. 71 Thus, the subtype of PDAC patients with DDR deficiency is sensitive to platinum analogs and PARP inhibitors.…”
Section: Parp Inhibitorsmentioning
confidence: 99%